Determination of pesticidal activity of decoctions and crude ethanol extracts from rhizomes of Zingiber officinale, stems of Tinospoa rumphii B. and leaves of Gliricidia sepium against Maize weevil, red flour beetle - Pueblos, Kirstin Rhys S.; Reyes, Arron Ernt V. (2014)
The increasing concern over the level of environmental and human health proplems caused by synthetic pesticides has encouraged researchers to look for alternative and safer organic pesticides. In this study, the decotions and crude ethanol extracts of Zingiber officianale, Tinospara rumphii Boerl and Gliricidia sepium were used to determine its insecticidal activity against maize weevils, red flour beetles and mosquito larvae. Contact and larvicidal bioassay methods were employed to determine the mortality rate of the plant extracts against the test samples at various concentrations and exposure time. The results revealed that the crude ethanol extracts were more efficient to beconsidered as an organic insecticide or larvicideas compared to its decoction counterparts. Generally, the decoction and crude ethanol extracts of the stem-bark of T. rumphii were considered as a potent pesticide against maize weevils, red flour beetles and mosquito larvae. In addition the red flour beetle has the highest mortality rate among the test organisms at various concentrations of all plant extracts. Concentration-dependent toxicity relationship was also observed in the larvicidal bioassay of all plant extracts used. The variability of the factors involved in each assay were statistically analyzed and proved to be significant with each other using one-way analysis of variance and univariate analysis.
Keywords: Natural pesticides